Pola Kebijakan Fiskal di ASEAN: Kontrasiklikal atau Prosiklikal? - Raisa Fitriaini (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
Fiscal policy is implemented by the government to influence the real sector through taxes and spending. Furthermore, government use It to mitigate the impact of the current business cycle in a country's economy (boom or depression) so fiscal policy indicates the government's commitment as an economic stabilizer. Referring to theory, fiscal policy should be countercyclical. However, it is possible that fiscal behavior is procyclical. This study determines the behavior of fiscal policy in ASEAN in the 2001-2018 period using the Panel Least Square (PLS). We estimate three models of fiscal behavior to examine the fiscal pattern. The estimation results show that the pattern of fiscal policy in ASEAN is countercyclical for models based on government revenue and fiscal balance, while model based on government revenue is procyclical.